2021
DOI: 10.1021/acsomega.1c03118
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Deposition-Prepared MIL-100(Cr)- and MIL-101(Cr)-Supported Iron Catalysts for Effectively Removing Organic Pollutants from Water

Abstract: Metal organic framework (MOF)-supported Fe catalysts belong to an important class of catalysts used for the advanced oxidation of organic pollutants in water. The successful preparation of the Fe/MIL-100­(Cr) and Fe/MIL-101­(Cr) catalysts in this work reinforced that a recently established carrier-gas free vapor deposition method can be a general one for preparing Fe/MOF catalysts. The Fe loading was in the range of 7.8–27.2 wt % on Fe/MIL-101­(Cr) at a deposition temperature of 110–150 °C, and it was only 4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…It has been reported in a study that iron-deposited MIL-101 (Cr) may lose its ability to adsorb after a few cycles because of crystal structure collapse. 50 This was likely due to iron deposition on the adsorbent, which was exacerbated at regeneration temperatures of 110−150 °C, as evidenced by the XRD plots in that study. Some solvents may degrade its performance as well.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported in a study that iron-deposited MIL-101 (Cr) may lose its ability to adsorb after a few cycles because of crystal structure collapse. 50 This was likely due to iron deposition on the adsorbent, which was exacerbated at regeneration temperatures of 110−150 °C, as evidenced by the XRD plots in that study. Some solvents may degrade its performance as well.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…Some solvents may degrade its performance as well. Nevertheless, the study reports a better stability performance for MIL-101 (Cr) than other adsorbents. In another study, a standalone MIL-101 (Cr) adsorbent packed bed column showed an excellent cyclic CO 2 adsorption capacity after regeneration for five cycles …”
Section: Resultsmentioning
confidence: 78%
“…20 Hence, heterogeneous Fenton's oxidation processes are a potential way to clean industrially polluted water even in a dark environment. 21 Several recent studies have been reported where pure and a combination of various catalysts were prepared by different methods such as by a Mn-doped Fe-based metal−organic framework (MOF), 22 BiOI/MIL-53(Fe) Z-scheme heterojunction (named BMFe) catalysts, 23 nano-FeO x /CN core− shell-structured catalyst, 23 Fe/MIL-100(Cr) and Fe/MIL-101(Cr) catalysts, 24 sulfidated Fe 3 S 4 @β-FeOOH, 25 core− shell-structured Mn 3 O 4 @SiO 2 NB, 26 magnetic Fe 3 O 4 as the core of a nitrogen-doped carbon (NC) matrix composite Fe 3 C (Fe 3 C/Fe 3 O 4 @NC), 27 nitrogen-doped carbon nanotube-encapsulated Fe 3 C (Fe 3 C@NCNT), 28 Fe cores (Fe@C) derived from CDM (catalytic decomposition of methane) particles, 29 Fe 3 O 4 @β-CD/g-C 3 N 4 β-cyclodextrin/graphitic carbon nitride, 30 Fe/Cu/zeolite catalysts, 31 and X-type zeolite molecular sieve catalysts modified with copper (Cu-X) catalysts. 32 A recent report from Yang et al showed that the nanocomposites containing FeS as a catalyst and MoS 2 as a co-catalyst creates a strong contact between the two components and yields a significant number of Mo 6+ sites and sulfur vacancies, which contribute to the enhanced degradation rate by accelerating Fe 3+ /Fe 2+ cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have been reported where pure and a combination of various catalysts were prepared by different methods such as by a Mn-doped Fe-based metal–organic framework (MOF), BiOI/MIL-53­(Fe) Z-scheme heterojunction (named BMFe) catalysts, nano-FeO x /CN core–shell-structured catalyst, Fe/MIL-100­(Cr) and Fe/MIL-101­(Cr) catalysts, sulfidated Fe 3 S 4 @β-FeOOH, core–shell-structured Mn 3 O 4 @SiO 2 NB, magnetic Fe 3 O 4 as the core of a nitrogen-doped carbon (NC) matrix composite Fe 3 C (Fe 3 C/Fe 3 O 4 @NC), nitrogen-doped carbon nanotube-encapsulated Fe 3 C (Fe 3 C@NCNT), Fe cores (Fe@C) derived from CDM (catalytic decomposition of methane) particles, Fe 3 O 4 @β-CD/g-C 3 N 4 β-cyclodextrin/graphitic carbon nitride, Fe/Cu/zeolite catalysts, and X-type zeolite molecular sieve catalysts modified with copper (Cu-X) catalysts …”
Section: Introductionmentioning
confidence: 99%